Very low-energy and low-fluence ion beam bombardment of naked plasmid DNA - R. Norarat (2018)
Ion beam bombardment of biological organisms has been recently applied to mutation breeding of both agricultural and horticultural plants. In order to explore relevant mechanisms, this study employed low-energy ion beams to bombard naked plasmid DNA. The study aimed at simulation of the final stage of the process of the ion beam bombardment of real cells to check whether and how very low-energy and low-fluence of ions can induce mutation. Argon and nitrogen ions at 5 keV and 2.5 keV respectively bombarded naked plasmid DNA pGFP to very low-fluences, an order of 1013ions/cm2. Subsequently, DNA states were analyzed using electrophoresis. Results provided evidences that the very low-energy and low-fluence ion bombardment indeed altered the DNA structure from supercoil to short linear fragments through multiple double strand breaks and thus induced mutation, which was confirmed by transfer of the bombarded DNA into bacteria Escherichia coli and subsequent expression of the marker gene. © 2009 Elsevier B.V. All rights reserved.